A review of the Libyan insolvency and restructuring laws informed by insolvency law theory and international benchmarks - Hosen, Emad-edden Rajab A. (Nottingham Trent University, 2020)
The research aims to evaluate the adequacy of the insolvency system in Libya to support the national desires and objectives identified in the country to enhance the national economy and to maintain social stability. The thesis considers the need for reform in the current business insolvency and rescue framework taking into account the country’s domestic circumstances. To conduct this evaluation, the research reviews the Libyan insolvency law by examining the theoretical approaches to corporate insolvency laws in order to understand the role that should be played, or the goal that should be reached, by the insolvency law. This is important to identify whether the insolvency and rescue laws should be concerned only about maximising economic interests or should be concerned also about wider societal interests and objectives. The study also undertakes an in depth evaluation of the current business insolvency and rescue framework by using the international benchmarks with particular reference to the UNCITRAL Legislative Guide on Insolvency Law. The thesis establishes that the current insolvency law is insufficient to promote the economic and social goals of the country because of both the deficiency of the legislative framework and inefficient institutions. The investigation reveals also that an application of the social justice theory as traditionally perceived by the Civil Code 1953 (as manifested in property law and contract law) that is primarily designed to achieve social goals (for example, the priority given to the wide-ranging category of privileged creditors over secured creditors) prevents the insolvency law from achieving the sought-after objectives leaving much to be desired for a reform. The research builds on these foundations to identify challenges and impediments to the development of the insolvency and rescue regime of Libya.
https://irep.ntu.ac.uk/id/eprint/41433/
Keywords: Company law; Corporate law; Insolvabilité; Insolvency; Libya; Procédures collectives; Restructuration; Restructuring law

The liquidation process and unsecured creditors: using the resulting trust to restore the balance - Stubbins, Matthew (Canterbury Christ Church University, 2020)
Ever since the formation of limited companies became permissible, unsecured creditors have faced a Sisyphean struggle to regularly recover substantial levels of the debts owed to them should corporate creditors enter insolvency. These low recovery rates result in many issues for lenders, including large losses, and in some cases, the insolvency of the lender themselves. The causes of these low return rates are long established and clearly demarcated. They consist of the existence and widespread use of security interests - which remove the majority of the company’s assets upon insolvency occurring - and the statutory priority of distribution, which ensures that parties other than the unsecured creditors have their debts discharged first by the liquidator from the already insufficiently resourced asset pool. English insolvency law has sought to provide some protection to the unsecured creditors through the anti-deprivation and personal liability provisions of the Insolvency Act 1986, which are intended to protect the integrity of the insolvent company’s asset pool. However, as concluded by this thesis, these provisions fail to afford adequate protection as a consequence of their substantive, evidential and remedial limitations, potentially resulting in the distributable assets being misappropriated and out of the reach of unsecured creditors. This thesis therefore analyses the limitations of the existing anti-deprivation and personal liability provisions before concluding as to how and why they fail to adequately protect unsecured creditors. This is done through a doctrinal and theoretical analysis of the provisions, before these conclusions are then tested empirically in two case studies. Given the inadequate protection provided by the Insolvency Act, this thesis then analyses the resulting trust – on which little analysis has been conducted in the context of insolvency – to determine whether it is capable of assisting unsecured creditors to increase their liquidation return rates. This increase is achieved through returning assets beneficially owned by the company to the company, or by preventing parties from becoming unsecured creditors in the first place by removing assets beneficially owned by them from the company. This analysis too will adopt a doctrinal and theoretical methodology, and it is concluded that the resulting trust is able to assist should the requisite factual matrices occur.
Permalink: https://repository.canterbury.ac.uk/item/8z4x2/the-liquidation-process-and-unsecured-creditors-using-the-resulting-trust-to-restore-the-balance
Keywords: Insolvabilité; Insolvency; Insolvência; Liquidation